Determinants of the quality of care relationships in long-term care - a systematic review - Aukelien Scheffelaar; Nanne Bos; Michelle Hendriks; Sandra van Dulmen; Katrien Luijkx (BMC, 2018)
Abstract Background The quality of a care relationship between a client and a care professional is seen as fundamental if high-quality care is to be delivered. This study reviews studies about the determinants of the quality of the client-professional relationship in long-term care. Methods A systematic review was performed using the electronic databases of Medline, Psycinfo, CINAHL and Embase. The review focused on three client groups receiving long-term care: physically or mentally frail elderly, people with mental health problems and people with physical or intellectual disabilities. Included studies concern clients receiving inpatient or outpatient care and care professionals who provided recurring physical and supporting care for a long period of time. The studies we included contained primary empirical data, were written in English and were published in peer-reviewed journals. Data extraction was carried out by two researchers independently. Results Thirty-two studies out of 11,339 initial hits met the inclusion criteria. In total, 27 determinants were revealed, six at the client level, twelve at the professional level, six between the client and care professional levels and three at the contextual level. The data analysis showed that most determinants were relevant in more than one client group. Conclusions This is the first review that looked at determinants of the quality of the care relationship for three large client groups receiving long-term care. It suggests that the current client group-specific focus in research and quality improvement initiatives for care relationships might not be needed. Care organisations can use the findings of this review as guidance on determinants to look for when mapping the quality of a care relationship in order to get a picture of specific points of attention for quality improvement.